PENGARUH LIMBAH PLAFON GIPSUM TERHADAP PENURUNAN KONSOLIDASI PADA TANAH LEMPUNG EKSPANSIF - Dewi, Ratna; Sutejo, Yulindasari; Rahmadini, Rizki; Arfan, Muhammad; Rustam, Reffanda Kurniawan (Jurusan Teknik Sipil dan Perencanaan Fakultas Teknik Universitas Sriwijaya, 2019)
Expansive clay has a high potential to swell if compared to other types of clay. Expansive clay also has very low bearing capacity so that a method of soil improvement was needed to improve the soil. This type of soil can be found in Gasing village, Tanjung Api-Api Km. 11 Banyuasin regency of South Sumatra Province. This research aims to study the mixture of gypsum plafond waste as additives in the process of stabilizing expansive soil clay. It can be made according to the needs of the mixture. In this study, the percentage of mixture of gypsum plafond waste are 5 %, 10 % and 15%. The test used an Oedometer (SNI 2812: 2011/ASTM D2435) equipment. By giving the pressure of 2.5 kN/m2; 5 kN/m2; 10 kN/m2; 20 kN/m2; and 40 kN/m2. The test results of the clay without mixture with gypsum plafond obtained were liquid limit value (LL) = 67%, plastic limit (PL) = 26.38% and plastic index value (PI) of 40.62%. Spesific Gravity (Gs) = 2.696, optimal water content (wopt) = 21.55 % and optimal dry weight (wopt) = 1.55 gr/cm3. Therefore, the soil sample was an expansive clay type and classified as A-7-6 (AASHTO classification). Consolidated test results show that soil compression index (Cc) = 0.190. After mixed with gypsum plafond waste of 15 %, the compression index value (cc) = 0.080. This indicates that the compression index value (cc) has decreased. Based on the above, it can be concluded that the mixture of gypsum waste in expansive clay causes soil settlement.